69 * 54 = 3 726
Chat with our AI personalities
3x2 + 33x + 54 =3(x2 + 11x + 18) = 3(x + 9)(x + 2)
15 + 14 + 14 + 11 + 2x + x = 75 Collect like terms 54 + 3x = 75 Subtract 54 3x = 21 Divide by 3 x = 7 ■
y=54 if x=6 so we can write y=9(x) so y=k(x) clearly y is directly proportional to x.
x=-9 15 + x = 6x + 60 x = 6x + 45 -5x = 45 x = -9 15 + (-9) = (6 * (-9)) + 60 15 - 9 = -54 + 60 6 = 60 - 54 6 = 6 There is no answer because, 15+x=6x+60 -15 -15 x=6x+45 Which is imposible because "x" can't equal itself times six plus forty-five.
9x + 8y = (9 x 6) + (8 x 3) = 54 + 24 = 78